Class Precarity and Solidarity in Education: Social Value Co-creation and Non-ownership Social Infrastructures - Hafiz, Abdul Aziz (PRISM: Casting New Light on Learning, Theory and Practice, 2018)
This paper builds on my previous work in this journal (Hafiz, 2017) on the potentialities of prosociality as a remedy and response to widespread precarity. The aim is to ground prosociality in co-operative social and educational practices rooted in the conscientisation of social and solidarity economy. Pedagogical practices based on principles of solidarity, reciprocity and sustainability can be directed to the production of knowledge (and its associated benefits) in order to meet the basic needs of food, energy, housing, energy production, social caring and well-being in general. This paper deepens the account of prosociality by treating it as a means for cooperation to produce social infrastructures that have a protective function. These infrastructures provide important underpinnings of a universal basic security to be delivered through a social and solidarity economy. I illustrate this from precarity in higher education in the North-West of England with particular reference to the widening participation agenda. This enables me to extend the previous analysis by linking it to the sociospatial complexities of class in higher education and precarity. Specifically, I argue that class differences should be analysed in relation to a differential relationship to the interrelated variables of global dependence – glocal potential that interact with the generative mechanisms of precarity.